Reconstruction of severe acetabular defects (Paprosky type III A) in total hip arthroplasty using modular tantalum augments in combination with a cemented cup - Spranz, David Maximilian; Müller, Lisa-Marie; Trefzer, Raphael; Hetto, Pit; Nees, Timo A.; Renkawitz, Tobias; Walker, Tilman; Reiner, Tobias (International orthopaedics, 2024)
Acetabular defect reconstruction can be a complex and challenging surgical procedure, with stable long-term fixation of the implants remaining the ultimate goal. The purpose of this study was (1) to evaluate the radiological and clinical outcome of complex acetabular reconstruction surgery with the use of modular tantalum TM augments in combination with cemented revision cups; (2) to investigate blood tantalum concentrations in these patients; and (3) to report complications and mechanisms of failure related to this procedure at mid-term follow-up (mean 4.5 years).